A course in electrical engineering volume i alternating currents - Dawes, Chester L. ([S.l.] : McGraw Hill Book Company Inc., 1934)
an update that gives more detail about AC power's application for electrical machinery. It discusses how to deal with this type of energy for series and parallel resonance, harmonics. It also discusses the conjugate methods for of computing both watts and vars.